Harnessing the Coordination Chemistry of 1, 4, 7‐Triazacyclononane for Biomimicry and Radiopharmaceutical Applications. Issue 7 (4th May 2018) - Joshi, Tanmaya; Kubeil, Manja; Nsubuga, Anne; Singh, Garima; Gasser, Gilles; Stephan, Holger
Abstract: 1, 4, 7‐Triazacyclononane (TACN)‐based mono‐ and poly‐nuclear metal complexes have found extensive use as biological mimics for understanding the structural and operational aspects of complex natural systems. Their coordination flexibility has also provided researchers access to a vast library of radiometal‐binding motifs that display excellent thermodynamic stability and kinetic inertness upon metal complexation. Synthetic modification of the TACN backbone has yielded ligands that can form metal complexes with coordination geometries well suited for these applications. In particular, Leone Spiccia's research has played a significant role in accelerating the progress in these two fields. With a focus on his contributions to the topics of biomimicry and radiopharmaceuticals, this Minireview uses relevant examples to put in perspective the utility of macrocyclic coordination chemistry for biological inorganic chemistry applications. Abstract : Coordination secured : The flexible coordination chemistry of 1, 4, 7‐triazacyclononane (TACN) derivatives has been widely exploited for generating macrocyclic metal complexes as good mimics of metal‐containing biosites and as metal‐based radiopharmaceuticals.